A preliminary analysis of the classical views of the concept of integration of knowledge - Mohd Amin, Wan Mohd Azam (Revelation and Science, IIUM, 2014)
This paper analyzes classical discourse on the integration of knowledge by Muslim scholars. This includes terminology offered in the jima‘ al-‘ilm and al-qiyas of Muhammad Idris al-Shafi‘i (d. 204/820); the ihya’ of Abu Hamid al-Ghazali (d. 505/1111); the ‘ilm al-sana’i‘ of Ibn Khaldun (d.806/1406); and the funun of al-Dihlawi (d.1176/1762) that pertain to the concept of the integration of knowledge. In-depth analysis of their writings reveals that they have already proposed the framework for knowledge integration that emphasizes the concept of soul, ma‘rifah, and their practical aspects. Their discussion of this framework has guided modern scholars to continue their noble efforts. Terms like Islamization (aslamat al-ma‘rifah), Islamicization (Islamiyyat al-ma‘rifah), and the integration (al-takamul) of human knowledge have been proposed by modern Muslim scholars whose aim is to continue the efforts made by their predecessors.